2024
DOI: 10.1021/acs.energyfuels.4c00750
|View full text |Cite
|
Sign up to set email alerts
|

Wetting Behavior of CO2–H2O–coal with Different Metamorphic Degrees under In Situ Thermophysical Conditions

Ke Li,
Chuanjie Zhu,
Xiangliang Zhang
et al.

Abstract: Wettability in CO2–H2O–coal directly determines pore-scale configuration and further affects practice projects on the hectometer scale; however, coal rank and thermophysical condition dependences of wettability and their underlying mechanisms are inadequate. Potential candidate coal beds (hvBb, hvAb, mvb, sa) were considered, and wettability reflected by static/dynamic contact angles was evaluated under in situ reservoir conditions (temperature and pressure) by the captive bubble method. Physicochemical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 101 publications
0
0
0
Order By: Relevance
“…Generally, an increase in coal rank increases the CO 2 wettability (Figure ); however, two distinct trends can be identified. For instance, a few studies ,,, found an increasing linear trend, i.e., a greater contact angle with increasing coal vitrinite reflectance while other studies , reported a fluctuating trend in contact angle with increasing vitrinite reflectance (i.e., an initial increase followed by a subsequent decrease) (Figure ). This could be attributed to the number of samples analyzed and their range of vitrinite reflectance.…”
Section: Coal Wettability Assessment By Contact Anglesmentioning
confidence: 99%
“…Generally, an increase in coal rank increases the CO 2 wettability (Figure ); however, two distinct trends can be identified. For instance, a few studies ,,, found an increasing linear trend, i.e., a greater contact angle with increasing coal vitrinite reflectance while other studies , reported a fluctuating trend in contact angle with increasing vitrinite reflectance (i.e., an initial increase followed by a subsequent decrease) (Figure ). This could be attributed to the number of samples analyzed and their range of vitrinite reflectance.…”
Section: Coal Wettability Assessment By Contact Anglesmentioning
confidence: 99%